2014
DOI: 10.1007/s00425-014-2120-4
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species produced via plasma membrane NADPH oxidase regulate anthocyanin synthesis in apple peel

Abstract: Solar ultraviolet irradiation regulates anthocyanin synthesis in apple peel by modulating the production of reactive oxygen species via plasma membrane NADPH oxidase instead of other pathways. The synthesis of anthocyanin in apple peels is dependent upon solar irradiation. Using 3-mm commercial glass to attenuate solar UV-A and UV-B light, we confirmed that solar UV irradiation regulated anthocyanin synthesis in apple peels after exposing previously bagged fruit to sunlight. During sunlight exposure, UV attenu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 70 publications
0
35
0
Order By: Relevance
“…Besides functioning in the regulation of pollen germination, root development and seed germination, as well as fungal development, NOXs/RBOHs have other effects as well. It was suggested that solar ultraviolet irradiation regulates anthocyanin synthesis in apple peel by modulating the production of ROS via NADPH oxidase [64]. Moreover, chloroplastic NADPH oxidase-like activity mediates perpetual H 2 O 2 generation, which probably induces apoptotic-like cell death of B. napus leaf protoplasts [65].…”
Section: Other Aspectsmentioning
confidence: 99%
“…Besides functioning in the regulation of pollen germination, root development and seed germination, as well as fungal development, NOXs/RBOHs have other effects as well. It was suggested that solar ultraviolet irradiation regulates anthocyanin synthesis in apple peel by modulating the production of ROS via NADPH oxidase [64]. Moreover, chloroplastic NADPH oxidase-like activity mediates perpetual H 2 O 2 generation, which probably induces apoptotic-like cell death of B. napus leaf protoplasts [65].…”
Section: Other Aspectsmentioning
confidence: 99%
“…Chloroplastic H 2 O 2 may activate FAH1 expression to induce anthocyanin accumulation (Maruta et al, 2014). If ultraviolet light is attenuated, the O 2 •concentration and the expression of anthocyanin biosynthesisassociated genes is reduced in apple peel (Zhang et al, 2014). ABA-induced H 2 O 2 is required for anthocyanin accumulation in the leaves of rice seedlings (Hung et al, 2008).…”
Section: Ros Especially H 2 O 2 and Omentioning
confidence: 99%
“…The production of ROS from plasma-membranelocalized NADPH oxidase plays an important role in ultraviolet ray (ultraviolet)-induced anthocyanin biosynthesis. If ultraviolet light is attenuated, the O 2 Áconcentration is reduced by the expression of anthocyanin biosynthesis-associated genes in Malus ¡domestica peel (Zhang et al, 2014). Chloroplastic H 2 O 2 may also activate FAH1 expression to induce anthocyanin accumulation (Maruta et al, 2014).…”
mentioning
confidence: 99%
“…Flavonoid biogenesis and/ or their regulatory pathway are involved in the resistance to various stresses, such as high and ultraviolet lights, low temperature, salinity, high sucrose and oxidation (Bharti et al, 2015;Ilk et al, 2015;Kusano et al, 2011;Lotkowska et al, 2015;Mahmood et al, 2016;Zhang et al, 2015). Flavonoids are powerful deoxidizers that relieve oxidative stress (Nakabayashi et al, 2014;Zhang et al, 2014), and respond quickly to different stresses (Dixon and Paiva, 1995). Plants may use flavonoids to deter the feeding, development and oviposition of herbivores (Onkokesung et al, 2014).…”
Section: Introductionmentioning
confidence: 99%